Heterodoxa dalam gerakan perlawanan perempuan Indonesia pada film “Kartini” - Bilhaq, Aulia Mardhatillah (UNIVERSITAS SARI MUTIARA INDONESIA, 2023)
Patriarchal culture is a culture that is inherent and developing in Indonesia. This culture assumes a position of power in the male group. Kartini as an Indonesian hero is known to be able to produce ideas that are resistance in nature and has succeeded in influencing the culture of domination that exists to this day. Even though Kartini lived at a time when power relations were very strong, especially at a time when Indonesia was still not independent. Kartini's struggle against male domination was immortalized in the film entitled